Seroprevalence of dengue amongst inhabitants of the semi-forested and forest fringe areas of peninsular Malaysia - J., Abd Jamil; Romano, Ngui; S., Nellis; H. A., Mohd Zan; R., Fauzi; L. Y., Chang; Yvonne Ai Lian, Lim; Sazaly, AbuBakar (Elsevier Inc., 2014)
Dengue is an endemic disease in the urban areas of the tropics and subtropics regions of the world. Its significance in the semi-forested and forest fringe areas, however, has not been well described. The present study investigated the seroprevalence of dengue amongst the indigenous or Orang Asli communities of peninsular Malaysia and correlated it with the population, socio-economic and geographical attributes of the communities’ surroundings.